Analysis Of The Ijarah Contract In The Practice Of Traditional Gold Ore Mill Rental In Hutabargot From The Perspective Of Islamic Economic Law - akhyar; Resi Atna Sari Siregar (Islamic Circle, 2025)
This study examines contractual practices within the rental system of traditional gold ore milling machines (gelundung) in Hutabargot District from the perspective of Islamic economic law. The rental agreement applied by the local community is generally conducted without a written contract and is based on customary practices (‘urf) that have been passed down through generations. This research aims to analyze the validity of the ijarah contract implemented in the gelundung rental practice and to assess its conformity with the principles of Islamic economic law. This study employs a qualitative approach with a field research method. Data were collected through direct observation, in-depth interviews with gelundung owners and renters, and documentation. The findings indicate that although the rental agreement is not explicitly stated in a formal contract, the essential pillars and conditions of the ijarah contract are substantively fulfilled, including the existence of contracting parties, the object of lease, the benefit derived, and the agreed compensation (ujrah). From the perspective of Islamic economic law, the gelundung rental practice in Hutabargot can be considered valid as it is grounded in recognized local custom (‘urf shahih) and does not contradict sharia principles. Therefore, this practice may continue to be applied with improvements in contractual clarity to enhance legal certainty without eliminating established local traditions.